(untitled) - Reed, Steven R. (Pittsburgh, 1993)
Takes on the task of demystifying Japanese culture and behaviour. Through examples that are familiar and his own personal encounters with the Japanese, Steven Reed argues that the apparent oddity of Japanese behaviour flows quite naturally from certain objective conditions that are different from those in the United States.
Keywords: Công nghiệp,Industries; Khía cạnh xã hội,Social aspects; Nhật Bản,Japan